CONSEQUENCES OF THE EUROPEAN SECURİTY AND DEFENSE POLICY FOR THE EUROPEAN NON-EU NATO MEMBERS - Çınar Özen (Ankara Avrupa Çalışmaları Dergisi)
The EU member States declared at the Cologne European Council in June 1999, their "determination to play a full role on the intemational stage and to obtaın the necessary means and capabılities regarding a coromon European policy on security and defence"* 1 and furthermore they defıned at the Helsinki Summit ın December 1999 the guidelines of a future European security and defence pohcy. The objective was to "create an autonomous capacity for the EU to take decisions and, where NATO as a whole is not engaged, to launch and then to conduct EU-led military operations in response to International crises"2.